THE EFFECT THE EFFECT OF SPREADING FACTOR ON LORA TRANSMISSION - Muhammad Khairin Nahwan; Dodon Turianto Nugrahadi; M. Itqan Mazdadi; Andi Farmadi; Friska Abadi (Fakultas MIPA Universitas Lambung Mangkurat, 2022)
The conditions of a different area can affect the transmission of data so that transmission is needed that is resistant to interference and in certain conditions a device that can monitor several places is needed at once. The concept of Wireless Sensor Network (WSN) is applied to meet these demands. This research is shown to determine the effect of Spreading Factor (SF) on Long Range (LORA) transmission on distance by analyzing Quality of Service (QOS). The test is divided into 2 conditions, namely: The Line of Sight (LOS) condition & Non-Line of Sight (NLOS) condition. The test results show that the maximum distance that the LoRa transmitter can reach is 1100m in LOS conditions while for NLOS conditions it can only reach a distance of 300m. The QOS parameters used to consist of Delay, Throughput, RSSI, & SNR. Spreading Factor (SF) affects Delay and Throughput, not RSSI and SNR. The best value of Delay (9.64 ms), Throughput (667.60 Bps), and RSSI ( -94.25 dBm) is at Spreading Factor (SF) 6 and SNR (5.23 dB) is Spreading Factor (SF) 8 and for the distance, the value of RSSI (-76.45 dBm) and SNR (5.23 dB) is at a distance of 10m. This applies in LOS and NLOS conditions.